Reduced in vivo toxicity of doxorubicin by encapsulation in cholesterol-containing self-assembled nanoparticles. (May 2016) - Gonzalez-Fajardo, Laura; Mahajan, Lalit H.; Ndaya, Dennis; Hargrove, Derek; Manautou, José E.; Liang, Bruce T.; Chen, Ming-Hui; Kasi, Rajeswari M.; Lu, Xiuling
Graphical abstract: Abstract: We previously reported the development of an amphiphilic brush-like block copolymer composed of polynorbornene-cholesterol/polyethylene glycol (P(NBCh9- b -NBPEG)) that self-assembles in aqueous media to form long circulating nanostructures capable of encapsulating doxorubicin (DOX-NPs). Biodistribution studies showed that this formulation preferentially accumulates in tumor tissue with markedly reduced accumulation in the heart and other major organs. The aim of the current study was to evaluate the in vivo efficacy and toxicity of DOX containing self-assembled polymer nanoparticles in a mouse xenograft tumor model and compare its effects with the hydrochloride non-encapsulated form (free DOX). DOX-NPs significantly reduced the growth of tumors without inducing any apparent toxicity. Conversely, mice treated with free DOX exhibited significant weight loss, early toxic cardiomyopathy, acute toxic hepatopathy, reduced hematopoiesis and fatal toxicity. The improved safety profile of the polymeric DOX-NPs can be explained by the low circulating concentration of non-nanoparticle-associated drug as well as the reduced accumulation of DOX in non-target organs. These findings support the use of P(NBCh9- b -NBPEG) nanoparticles as delivery platforms for hydrophobic anticancer drugs intended to reduce the toxicity of conventional treatments.